Effect of stored oil palm trunk sap towards methyl ester synthesis / Nurnuha Shamsir ... [et al.] - Shamsir, Nurnuha; Abu Jahar, Noorhasmiera; Zakaria, Sarani; M Aizat, Wan; Ling, Pua Fei; Syed Jaafar, Sharifah Nabihah (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
Oil palm trunk (OPT) has highest content of sap, 80% of the overall weight. OPT sap contains free sugars which can be converted into valuable compounds such as ester. The objective of this study is to determine the changes of free sugars at different storage time and the effect on methyl ester synthesis. The sap was extracted and stored at different durations time (1, 7, 14, 21 and 28 days). 10ml of dried sap was added with 100mg Fe2(SO4)3 EFB and 15ml of methanol. The mixture was put into the autoclave to be heated at 160 oC for 150 minutes. Free sugars found in OPT sap were glucose, fructose and sucrose. The free sugars vary upon the storage time and highest concentration of glucose and fructose achieved at day 21. This is due to hydrolysis of sucrose. The GC-MS analysis identified and quantified several methyl ester such as methyl pyruvate, methyl levulinate, methyl-9- oxononanoate and methyl palmitate. These findings confirmed that the free sugars from OPT sap were possible to be an alternative carbon in ester synthesis